Practical Information Security A Competency-Based Education Course - Alsmadi, Izzat (Springer International Publishing, 2018)
This textbook presents a practical introduction to information security using the Competency Based Education (CBE) method of teaching. The content and ancillary assessment methods explicitly measure student progress in the three core categories: Knowledge, Skills, and Experience, giving students a balance between background knowledge, context, and skills they can put to work. Students will learn both the foundations and applications of information systems security; safeguarding from malicious attacks, threats, and vulnerabilities; auditing, testing, and monitoring; risk, response, and recovery; networks and telecommunications security; source code security; information security standards; and compliance laws. The book can be used in introductory courses in security (information, cyber, network or computer security), including classes that don't specifically use the CBE method, as instructors can adjust methods and ancillaries based on their own preferences. The book content is also aligned with the Cybersecurity Competency Model, proposed by department of homeland security. The author is an active member of The National Initiative for Cybersecurity Education (NICE), which is led by the National Institute of Standards and Technology (NIST). NICE is a partnership between government, academia, and the private sector focused on cybersecurity education, training, and workforce development.